2016
DOI: 10.1093/gji/ggw075
|View full text |Cite
|
Sign up to set email alerts
|

Statistical estimation of the duration of aftershock sequences

Abstract: S U M M A R YIt is well known that large earthquakes generally trigger aftershock sequences. However, the duration of those sequences is unclear due to the gradual power-law decay with time. The triggering time is assumed to be infinite in the epidemic type aftershock sequence (ETAS) model, a widely used statistical model to describe clustering phenomena in observed earthquake catalogues. This assumption leads to the constraint that the power-law exponent p of the Omori-Utsu decay has to be larger than one to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Consequently, declustering methods, which aim to recover the triggering structure, would always suffer from the bias in truen^ if they showed perfect performance. We described the temporal decay with the standard modified Omori formulation; for different formulations, e.g., a truncated power law decay [ Hainzl et al ., ] or stretched exponential [ Mignan , , , ], we expect a different size of the bias.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, declustering methods, which aim to recover the triggering structure, would always suffer from the bias in truen^ if they showed perfect performance. We described the temporal decay with the standard modified Omori formulation; for different formulations, e.g., a truncated power law decay [ Hainzl et al ., ] or stretched exponential [ Mignan , , , ], we expect a different size of the bias.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, it is important to stress that although our findings suggest that ETAS-type models can, at the very least, serve as a legitimate alternative view of seismicity, there are still some unresolved open issues and certainly room for further refinement. Several authors have reported sources of bias related to the lower magnitude cut-off (Harte, 2016; Schoenberg et al, 2010; Seif et al, 2017; Wang et al, 2010), the finite catalog length and the duration of sequences (Hainzl et al, 2016; van der Elst, 2017; Wang et al, 2010), aftershock incompleteness (e.g. Hainzl et al, 2013; Seif et al, 2017; Zhuang et al, 2017), potential time-dependence of the background rate (Hainzl et al, 2013), the use of an isotropic kernel for the spatial distribution of direct aftershocks (Bach and Hainzl, 2012; Guo et al, 2015; Hainzl et al, 2008), sample size (Harte, 2018) and potential spatial, temporal, and intersequence variability of parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…aftershock) within the same cluster, only when h > 0. Hence, mean field models are unable to generate the superposition of complex triggering trees identified in natural phenomena [72,73,99,100] and modeled in spatio-temporal stochastic point processes [71,87,101]. Instead, all aftershocks triggered due to the breaking of a given fiber S k are correlative in time and occur in the same cluster.…”
Section: The Origin Of Aftershocksmentioning
confidence: 99%